2002
DOI: 10.1007/bf03176765
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational connections enhance the personal/social development of young children

Abstract: In the last four decades changes have occurred that have resulted in the virtual disappearance ofthe extendedfamily, and dramatic decrease in the amount ofsignificant interactions between generations. America has become more mobile, widening the geographic and emotional separation between children and senior adults, creating a societal "health" problem -disconnectedness.Traditionalfamilial tasks (caringfor the children and elderly) are now delegated to institutions outside the home; childcare centers and nursi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 4 publications
1
17
0
Order By: Relevance
“…After removing the duplicates and irrelevant results, we obtained 55 articles for full text review. The final selection obtained 27 sources ( Figure 1) (Camp et al, 1997;Newman, 1997;Travis et al, 1997;Bales et al, 2000;Middlecamp and Gross, 2002;Rosebrook, 2002;Scott et al, 2005;Epstein and Boisvert, 2006;Ayala et al, 2007;Reisig and Fees, 2007;Holmes, 2009;Doll and Bolender, 2010;Belgrave, 2011;Heyman et al, 2011;Jarrott and Smith, 2011;Kamei et al, 2011;Morita and Kobayashi, 2013;Isaki and Harmon, 2014;Skropeta et al, 2014;Low et al, 2015;Murayama et al, 2015;Thompson and Weaver, 2015;Varma et al, 2015;Sakurai et al, 2016;Teater, 2016;Yasunaga et al, 2016). Ten studies assessed the impact of IG programs upon children (Newman, 1997;Bales et al, 2000;Middlecamp and Gross, 2002;Rosebrook, 2002;Holmes, 2009;Heyman et al, 2011;Kamei et al, 2011;Isaki and Harmon, 2014;Thompson and Weaver, 2015;Yasunaga et al, 2016), 15 referred to the elder population (Ca...…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…After removing the duplicates and irrelevant results, we obtained 55 articles for full text review. The final selection obtained 27 sources ( Figure 1) (Camp et al, 1997;Newman, 1997;Travis et al, 1997;Bales et al, 2000;Middlecamp and Gross, 2002;Rosebrook, 2002;Scott et al, 2005;Epstein and Boisvert, 2006;Ayala et al, 2007;Reisig and Fees, 2007;Holmes, 2009;Doll and Bolender, 2010;Belgrave, 2011;Heyman et al, 2011;Jarrott and Smith, 2011;Kamei et al, 2011;Morita and Kobayashi, 2013;Isaki and Harmon, 2014;Skropeta et al, 2014;Low et al, 2015;Murayama et al, 2015;Thompson and Weaver, 2015;Varma et al, 2015;Sakurai et al, 2016;Teater, 2016;Yasunaga et al, 2016). Ten studies assessed the impact of IG programs upon children (Newman, 1997;Bales et al, 2000;Middlecamp and Gross, 2002;Rosebrook, 2002;Holmes, 2009;Heyman et al, 2011;Kamei et al, 2011;Isaki and Harmon, 2014;Thompson and Weaver, 2015;Yasunaga et al, 2016), 15 referred to the elder population (Ca...…”
Section: Resultsmentioning
confidence: 99%
“…Differently, a trial performed in Ohio, compared social and personal skills between preschool children involved in IG programs and preschool children not involved in similar activities (Rosebrook, 2002). This study, including 200 children, showed that IG childcare enhanced personal/social development in preschoolers (Rosebrook, 2002).…”
Section: Impact On Children Participantsmentioning
confidence: 89%
See 3 more Smart Citations